Paranoid Schizophrenia: Case Report - Subagyo, Roni; Prasetya, Era Catur; Hamida, Anisatul; Rafida, Maya; Ramzi, Muhammad; Nugraha, Muhammad Tegar; Haniifah, Ulaa; Anas, Muhammad (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2022)
Background: The prevalence of schizophrenia in Indonesia is 1.7 per 1000 population, while the highest prevalence is in DI Yogyakarta and the Special Region of Aceh, where the incidence is 2.7 per 1000. Case Report: To discuss the treatment of Paranoid Schizophrenia with medication given previously due to relapse and disturbing the surrounding environment. Method: Reporting a case of a 32-year-old patient who came with his family in a state of anger, especially when he heard unpleasant talks about himself, and always felt watched his movements by others. The patient was diagnosed with Paranoid Schizophrenia and relapsed with risperidone 2x2 mg, trihexyphenidyl 2x2mg, and clorilex 1x12.5mg. Conclusion: Schizophrenia is a severe mental disorder (psychotic) because sufferers experience disturbances in assessing reality, lose contact with reality, and are characterized by significant disturbances in thought content (delusions), perceptual disturbances (hallucinations), and emotional and behavioral disturbances. In paranoid schizophrenia, delusions and/or hallucinations are very prominent. Management of people with schizophrenia includes the provision of psychopharmaceutical drugs, psychological therapy, and psychosocial therapy. No single approach can meet all the needs of people with schizophrenia.Keyword : Schizophrenia, paranoid, relapsed, treatment, environment